The things we do for love - Hannah, Kristin (New York : Ballantine Books, 2004)
A poignant, evocative story that celebrates the magic of motherhood, the joys of coming home, and the price we so willingly pay for love.
Keywords: Divorced women -- Fiction; Female friendship -- Fiction; Restaurateurs -- Fiction; Teenage girls -- Fiction; Aging parents -- Fiction; Restaurants -- Fiction; Psychological fiction; Domestic fiction